Welcoming the Stranger with Intention and Architectural Edifice: Beyond the Geopolitical Hollowness of Crimmigration - du Toit, Calvyn Clarence (International journal of public theology, 2016)
Encounters between strangers and established dwellers harbour poetic possibilities. However, contemporary cities often fail to capitalise on these meetings. Events of crimmigration divulge a geopolitical hollowness, which the city might reframe. This article offers such a reframing by discoursing Public Theology and Architecture. First, we describe the geopolitical hollowness of crimmigration. Next, we connect Spiritual Architecture and Public Theology through Stiegler’s description of the pharmacological atmosphere technics engender. Then, we interpret a biblical spirituality curated by the Sodom narrative, illuminating the pathological paths which established denizens’ desire for the migrant might take. Finally, inspired by amalgamating the architect, Norberg-Schulz’s ‘art of place’ and the potential for an architectural ‘art of care’ dormant in Heidegger’s philosophy, we propose a symbolic architectural edifice. A building welcoming and inviting the care-filled contribution of the migrant to the node of the city.